STRATEGY TO BUILD BRAND IMAGE TO INCREASE COMPETITIVENESS AT SMK SYUBBANUL WATHON SECANG - Nurfiati, Alma; Dahlia, Dahlia; Aini, Qurotul (Universitas Islam Negeri (UIN) Sumatera Utara, 2025)
The decline in applicant interest and weak public trust in vocational schools pose serious challenges to vocational education in Indonesia. This study examines the brand image development strategies at SMK Syubbanul Wathon Secang, a pesantren-based vocational school in Magelang Regency, as well as the challenges faced in enhancing the school's competitiveness. The research subjects consisted of five informants, including the principal, vice principals for curriculum and student affairs, and several teachers directly involved in school branding activities. The object of the study was the school's branding strategies implemented in digital, academic, and religious aspects. This study employed a qualitative method with a case study approach. Data were analyzed thematically using the Miles, Huberman, and Saldana model and validated through source triangulation and member checking. The results indicate that the main strategies include improving the quality of vocational programs, utilizing social media, organizing student work exhibitions, engaging alumni and school ambassadors, and strengthening religious values as the school's distinctive identity. These strategies align with Keller's brand image theory, emphasizing the importance of strong, favorable, and unique brand associations. The challenges faced include limited digital human resources, minimal promotional budgets, inter-school competition, and low public awareness of the importance of school image. The study's implications contribute theoretically to Islamic education management literature and offer practical recommendations for developing branding strategies in other pesantren-based vocational schools.